Community Dakwah Program @Xkwavers Against the Religiosity of Korean Wavers High School Level Muslim Students - Hilda Rafika Waty; Budi Handrianto; Wido Supraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
One of popular cultures which has a public attention and has spread to various countries, including Indonesia, is the Korean Wave culture. Mostly of Korean Wave lovers are immersed in loving their idols, making barriers to self upgrading, especially in their Islamic quality. This study aims to analyze the da'wah program of the Xkwavers community on the religiosity of Korean Wavers Senior High School level Muslim students. This research method used a descriptive quantitative by observation, interview and literature study. This study used a questionnaire with 108 Korean Wavers muslim who participated by a Likert Scale and religiosity by MUDRAS question items scale. The results showed that 51.9% are active Korean Wavers and showed that 62% of respondents were that Korean Wave culture had a balanced positive and negative impact, 20.4% stated that there were more negative impacts and 17.6% stated that they had a positive impact. The other results are also showed by the religiosity of respondents at Senior High School level which is described in the best worship percentage shown in the obligatory prayers on time. The xkwavers community missionary program came to invite Korean Wavers to study religion more deeply. The results showed that respondents who join in xkwavers program had an increased in religiosity by 33.26% likes the close relationship with Allah and the Prophet.